Case report - Novelis Italy - Belluigi, Valentina (La Medicina del Lavoro, 2020)
Introduction: A 55 years old employee of a multinational engineering company producing aluminum ribbons and alloys. Mill inspector on three shifts. Objectives: In 2009 during a periodic evaluation he presented a BMI of 32.9. The plant occupational health physician sent him to the Obesity Center at “Clinica del Lavoro” in Milan, but the employee wasn’t motivationally engaged. Methods: In August 2012 a Public Psychiatric Center diagnosed him with mood disorder and suggested to avoid night shifts. He began psychiatric therapy and a three-month medical follow-up in the plant. In September 2013, as recommended by the Psychiatric Center, he restarted to gradually work night shifts, for not more than two or three nights a months. In July 2017 he spontaneously went to the Obesity Center presenting a BMI of 42.78. This was the diagnosis: “Third class obesity with metabolic syndrome, diabetes type 2 at first comparison, dyslipidemia, suspected sleep apnea syndrome”. New examination in the center in January 2018: “Second class obesity with weight decrease in previous third class obesity and metabolic syndrome”. Adequate adherence to therapy and improving of dysfunctional eating behaviors. Results: New control January 2019:”Further weight decrease (25 kg), diabetes type 2 in a good metabolic control”. Discussion: Over the years, thanks to the continuous sensibilization during medical examinations and through some preventive health campaigns, thanks especially to the collaboration of specialized high level hospital centers, we have achieved a therapeutic success associated with an increase of working performance.